Correction: Serum biomarker for diagnostic evaluation of pulmonary arterial hypertension in systemic sclerosis. - Rice, Lisa M.; Mantero, Julio C.; Stratton, Eric A.; Warburton, Rod.; Roberts, Kari.; Hill, Nicholas.; Simms, Robert W.; Domsic, Robyn.; Farber, Harrison W.; Lafyatis, Robert. (Tufts University. Tisch Library., 2022)
Springer Open.